Differential effects on membrane permeability and viability of human keratinocyte cells undergoing very low intensity megasonic fields. Issue 1 (December 2017) - Domenici, F.; Brasili, F.; Giantulli, S.; Cerroni, B.; Bedini, A.; Giliberti, C.; Palomba, R.; Silvestri, I.; Morrone, S.; Paradossi, G.; Mattei, M.; Bordi, F.
Abstract Among different therapeutic applications of Ultrasound (US), transient membrane sonoporation (SP) - a temporary, non-lethal porosity, mechanically induced in cell membranes through US exposure - represents a compelling opportunity towards an efficient and safe drug delivery. Nevertheless, progresses in this field have been limited by an insufficient understanding of the potential cytotoxic effects of US related to the failure of the cellular repair and to the possible activation of inflammatory pathway. In this framework we studied thein vitro effects of very low-intensity US on a human keratinocyte cell line, which represents an ideal model system of skin protective barrier cells which are the first to be involved during medical US treatments. Bioeffects linked to US application at 1 MHz varying the exposure parameters were investigated by fluorescence microscopy and fluorescence activated cell sorting. Our results indicate that keratinocytes undergoing low US doses can uptake drug model molecules with size and efficiency which depend on exposure parameters. According to sub-cavitation SP models, we have identified the range of doses triggering transient membrane SP, actually with negligible biological damage. By increasing US doses we observed a reduced cells viability and an inflammatory gene overexpression enlightening novel healthy relevant strategies.